2020
DOI: 10.1007/s42690-020-00213-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tools-advances, opportunities and prospects for the control of parasites of veterinary importance

Abstract: The recent advancement in genome sequencing facilities, proteomics, transcriptomics, and metabolomics of eukaryotes have opened door for employment of molecular diagnostic techniques for early detection of parasites and determining target molecules for formulating control strategies. It further leads to the introduction of several purified vaccines in the field of veterinary parasitology. Earlier, the conventional diagnostic methods was entirely based upon morphological taxonomy for diagnosis of parasites but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…majus isolate not only adds new information to the body of knowledge regarding South African soil fungal biodiversity, but opens the way for developing this organism as a product in the local agricultural industry. It has been shown that local strains are generally more effective biocontrol agents, as they are adapted to local environmental conditions, and many regions are tapping into local biodiversity as a source of biopesticides [ 8 , 28 , 29 ]. The presence of M .…”
Section: Discussionmentioning
confidence: 99%
“…majus isolate not only adds new information to the body of knowledge regarding South African soil fungal biodiversity, but opens the way for developing this organism as a product in the local agricultural industry. It has been shown that local strains are generally more effective biocontrol agents, as they are adapted to local environmental conditions, and many regions are tapping into local biodiversity as a source of biopesticides [ 8 , 28 , 29 ]. The presence of M .…”
Section: Discussionmentioning
confidence: 99%
“…In the era of low-cost genome sequencing, this should be a priority, especially for species that are rare and in danger of being lost. The advantages of having a greater representation of the overall genetic diversity of schistosomes are bound to be many and will include clues as to how life cycles are orchestrated [ 159 ], why some species have broader host spectra than others [ 160 , 161 ], how host shifts might have been undertaken [ 162 , 163 ], how genetically diverse particular species are [ 164 , 165 ], and how we might reveal targets that would make their management more likely [ 166 ].…”
Section: Outlook and Priorities For Future Workmentioning
confidence: 99%
“…Insects, rodents, and to some extent, pets are an integral component of societies in the developing regions of Asia, South America, and Africa [ 7 , 235 ]. For example, both edible insects, rodents, and other wild animals contribute significantly to household food security and nutrition [ 236 , 237 ]. Companion animals, including cats and dogs, are also common, where the latter is even used for household security and hunting edible wild animals.…”
Section: Human Exposure and Health Risksmentioning
confidence: 99%